Queer International Relations : Sovereignty, Sexuality and the Will to Knowledge - Weber, Cynthia (New York Oxford University Press, 2016)
"This book puts International Relations scholarship and Queer Studies scholarship in conversation to tell a story about how sovereignty and sexuality are entangled in international relations theory and policy through numerous figurations of 'the homosexual' - as 'the underdeveloped', 'the un-developable', 'the unwanted im/migrant', 'the terrorist', 'the gay rights holder', 'the gay patriot' and Eurovision-winner Conchita Wurst's 'bearded lady'
Include Bibliography and Index
Keywords: Social science -- Queer theory -- International relations--Social aspects